Farmer’s Management Practices Adopted Against Mustard Aphid, Lipaphis erysimi (Kalt.): A Survey of Chitwan, Nepal - Kafle, Kapil; Jaishi, Mahesh (International Journal of Applied Sciences and Biotechnology, 2020)
Insect pests are the major constraints of crop production. Mustard aphid is the major problems of rapeseed contributing mustard decline in Chitwan, Nepal. Semi-structured questionnaire survey was conducted on randomly selected farmers of Chainpir Village Development Committee (VDC), Chitwan after a pre-testing in Mangalpur VDC to study the farmers’ knowledge and management practices adopted against mustard aphid in Chitwan. Study revealed majority (60%) of the respondent suggested aphid as the major insect of rapeseed and moreover, 86% of the respondent experienced it to cause 25% loss to the crop yield. Much proportion of respondents (58%) also realized low temperature with high humidity at the time of flowering as a cause in higher aphid infestation. Farmers use 2-3 sprays of chemical insecticide to control aphid but was found to destroy natural enemies and bee population besides damaging natural environment and human health. Int. J. Appl. Sci. Biotechnol. Vol 8(1): 78-82